2017
DOI: 10.4236/ojbd.2017.73009
|View full text |Cite
|
Sign up to set email alerts
|

Using of Color Model and Contrast Variation in Wavelet Ideology for Study <i>Megaloblastic Anemia Cells</i>

Abstract: Processing and analyzing of medical images is one of the priority research areas. At the same time, the processing of images of cells occupies a special place. This is due to the fact that such studies allow for a comprehensive diagnosis of the state of human health, identify and prevent the development of diseases in the early stages. We investigate the effectiveness of using wavelet analysis in color models, taking into account the preliminary change in the contrast of the input image. We consider the HSV co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In this way most systems for medical images recording and analyzing work [9]. But for analysis we can use other systems of color image, for example, it can be HSV color system: channels-H (hue), S (saturation), V (volume or brightness) [12]. Such a transition allows us to emphasize the features of the cellular structure because of the difference in perception and representation of the image points for different color spaces.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this way most systems for medical images recording and analyzing work [9]. But for analysis we can use other systems of color image, for example, it can be HSV color system: channels-H (hue), S (saturation), V (volume or brightness) [12]. Such a transition allows us to emphasize the features of the cellular structure because of the difference in perception and representation of the image points for different color spaces.…”
Section: Resultsmentioning
confidence: 99%
“…We apply the method of histogram change in the specified range with gamma correction. We conducted studies that showed that the histogram change in the specified range with gamma correction combined with the conversion of color space from RGB to HSV increases the contrast of the original image by an order in comparison with other methods [12]. This result is associated with emphasizing the low contrast areas of the original image due to non-linear transformation of the original image (color space modification) and subsequent non-linear correction of the converted image.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations